Capacidad antifúngica de la medicarpina sobre hongos xilófagos y patógenos de árboles maderables - Ayala Ponce, Rafael (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
This research evaluated the antifungal activity of the ethyl acetate extract and (+)-mediccarpine, obtained from the Duramen of Andira inermis (river almond). The removable was obtained by the soxhlet method, determining an optimal performance of 3.77 g/60 g of duration at 10 h of reflux, which subsequently to the process of purification and quantification of (+)-mediccarpine by thin layer chromatography and spectrophotometry, showed a content of 4.3 mg/mL of (+)-medicarpin. The purification of (+)-medicarpin was performed by column chromatography with mixtures of ethyl acetate and hexane, with confirmation of its purity with nuclear magnetic resonance (RMN-¹H). In vitro antifungal activity was determined with both extract and (+)-medicarpin at different concentrations (0.5, 1, 2.5, 5, 7.5 and 10 mg/mL), on the micellial growth of two phytopathogens fungi (Fusarium solani and Alternaria solani) and three xylophagous fungi (Trametes versicolor, Irpex lacteus and Phlebiopsis sp.). The agar well diffusion method was used, with methanol as a dilution vehicle (negative control) and the commercial fungicide benomyl [1-(butylcarbamoil) benzimidazole-2-ylcarbamate methyl] at 1 mg/mL (positive control). At 8 days of incubation in PDA (papa-dextrose-agar), at 28 ºC in dark conditions, inhibition percentages were obtained and the minimum inhibitory concentration (MIC) of both extract and (+)-medicarpin, as well as CL50 and CL100, were established. The extract showed 100% inhibition on xylophagous fungi, with a MIC of 0.05 mg/mL and relatively low CL50 and CL100 values on T. versicolor and Phlebiopsis sp. (CL50=0.11 mg/mL and CL100=0.24 mg/mL) and on I. lacteus (CL50=0.28 mg/mL and CL100=0.69 mg/mL). However, the inhibition of extract in phytopathogenic fungi was less, obtaining a higher 0.25 mg/mL MIC and CL50 and CL100 values for both A. solani (CL50=0.39 mg/mL and CL100=0.87 mg/mL) and for F. solani (CL50=0.41 mg/mL and CL100=0.98 mg/mL).

En esta investigación se evaluó la actividad antifúngica del extracto con acetato de etilo y (+)-medicarpina, obtenidos del duramen de Andira inermis (almendra de río). El extracto se obtuvo por el método Soxhlet, determinando un óptimo rendimiento de 3.77 g/60 g de duramen a la 10 h de reflujo, que posteriormente al proceso de purificación y cuantificación de (+)-medicarpina por cromatografía en capa fina y espectrofotometría, mostró un contenido de 4.3 mg/mL de (+)-medicarpina. La confirmación de la pureza de la (+)-medicarpina se realizó con el compuesto aislado por cromatografía en columna con mezclas de acetato de etilo y hexano, utilizando resonancia magnética nuclear (RMN-¹H). La actividad antifúngica in vitro se determinó tanto con el extracto como con (+)-medicarpina en diferentes concentraciones (0, 0.05, 0.1, 0.25, 0.5, 0.75 y 1 mg/mL), sobre el crecimiento micelial de tres hongos xilófagos (Trametes versicolor, Irpex lacteus y Phlebiopsis sp.) y dos fitopatógenos (Fusarium solani y Alternaria solani). Se utilizó el método de difusión en agar con pozos, usando metanol como vehículo de dilución (control negativo) y el fungicida comercial benomilo a 1 mg/mL (control positivo). A los 8 días de incubación en medio PDA (papa-dextrosa-agar), a 28 °C en condiciones de oscuridad, se evaluaron los porcentajes de inhibición y se estableció la concentración mínima inhibitoria (CMI) tanto del extracto como de la (+)-medicarpina, así como la CL50 y CL100. El extracto mostró un 100% de inhibición sobre los hongos xilófagos, con una CMI de 0.05 mg/mL y valores de CL50 y CL100 relativamente bajos en T. versicolor y Phlebiopsis sp (CL50=0.11 mg/mL y CL100=0.24 mg/mL) y en I. lacteus (CL50=0.28 mg/mL y CL100=0.69 mg/mL). Sin embargo, la inhibición del extracto en los hongos fitopatógenos fue menor, obteniendo una CMI de 0.25 mg/mL y valores de CL50 y CL100 más altos tanto para A. solani (CL50=0.39 mg/mL y CL100=0.87 mg/mL) como para F. solani (CL50=0.41 mg/mL y CL100=0.98 mg/mL).
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2020-0794; Andira inermis; Antifúngicos; Hongos fitopatógenos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2685